If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(3x + -7) = 24 Reorder the terms: -1(-7 + 3x) = 24 (-7 * -1 + 3x * -1) = 24 (7 + -3x) = 24 Solving 7 + -3x = 24 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -3x = 24 + -7 Combine like terms: 7 + -7 = 0 0 + -3x = 24 + -7 -3x = 24 + -7 Combine like terms: 24 + -7 = 17 -3x = 17 Divide each side by '-3'. x = -5.666666667 Simplifying x = -5.666666667
| 2v-5=-10 | | (x-3)(1-x)=1 | | 3(6-x)=3 | | 12+8x-12x+6=-122 | | 4j=3.6 | | 3(y+2)+y=15-(y-4) | | 6p-6=7p-7 | | 25x+10y=405 | | 3(7-x)=12 | | 8=-4(3x-4) | | -x-6x+7=42 | | 9-3(x-4)=36 | | -62=5x+3 | | 18+2x/3=16 | | 24=(2x-3) | | 3w-3=4w+8 | | 4(7-x)=4 | | (78+x)+x=434 | | 4.9t^2-13.5t=66 | | 3n=-27 | | 4x^2+18x+14=0 | | -8+6x=38 | | 22x*15*13x= | | 0.6x+3-2x=7x+3 | | 4x-6=6(x+2)+8 | | 9x-4=2x-3 | | 8b+6(-6-2b)=4+b | | x-5+x-5+x-5+x-5=12+x+x | | 2x-3=2(x+4) | | 18(w+3)-45=18+54 | | 25-7a=28+4a | | 5x^4-30x^2= |